Isolation of persistent left superior vena cava during atrial fibrillation ablation - Ozcan, Emin E. (Indian Pacing Electrophysiol J, 2015)
Persistent left superior vena cava is a rarely seen anomaly but it may be an arrhythmogenic source for paroxysmal atrial fibrillation. Furthermore, the complex anatomicregion between the left superior vena cava and the pulmonary veins may leads to misinterpretation of the pulmonary vein recordings during atrial fibrillation ablation. Approaches that might be helpful to overcome these problems are discussed in this case report.